2016
DOI: 10.1002/prp2.261
|View full text |Cite
|
Sign up to set email alerts
|

Soluble guanylate cyclase redox state under oxidative stress conditions in isolated monkey coronary arteries

Abstract: Coronary artery disease is associated with oxidative stress due to the excessive generation of free radicals in the vascular wall. This study investigated the impact of tert‐butyl hydroperoxide (t‐BuOOH), a peroxyl radical generator, on the redox state of soluble guanylate cyclase (sGC) in isolated monkey coronary arteries. Helically cut strips of endothelium‐intact monkey coronary arteries treated with the nitric oxide synthase inhibitor NG‐nitro‐L‐arginine (10 μmol/L) were exposed for approximately 60 min to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…In sGC stimulator, activator, and NO-containing systems, it was found that intracellular superoxide could scavenge NO and shift the sGC redox equilibrium while extracellular superoxide reacted with NO only outside the cell [54]. ROS-mediated shift of the sGC heme redox equilibrium towards the Fe 3+ state greatly reduced the activity of the signaling pathway [58]. While many of these studies were conducted in rats [5355], increased oxidative stress due to a peroxyl radical generator in isolated monkey coronary arteries also resulted in a disruption in the sGC redox state, demonstrating the importance of heme regulation in nonhuman primates as well [58].…”
Section: Heme Regulation Of Sgcmentioning
confidence: 99%
“…In sGC stimulator, activator, and NO-containing systems, it was found that intracellular superoxide could scavenge NO and shift the sGC redox equilibrium while extracellular superoxide reacted with NO only outside the cell [54]. ROS-mediated shift of the sGC heme redox equilibrium towards the Fe 3+ state greatly reduced the activity of the signaling pathway [58]. While many of these studies were conducted in rats [5355], increased oxidative stress due to a peroxyl radical generator in isolated monkey coronary arteries also resulted in a disruption in the sGC redox state, demonstrating the importance of heme regulation in nonhuman primates as well [58].…”
Section: Heme Regulation Of Sgcmentioning
confidence: 99%
“… 52 Alternative mechanisms of soluble GC activation by oxidant molecules described in other cell types are likely to underlie the effect of platelet NOXs on intracellular cGMP. 53 , 54 …”
Section: Discussionmentioning
confidence: 99%
“…Though, we observed a significant decrease in aortic soluble guanylate cyclase (sGC) subunits being accompanied by the reduced phosphorylation of VASP at Ser239, a surrogate marker of PKG [36]. sGC is important in NO signaling, commonly referred as the “NO receptor.” However, sGC is an enzyme which is highly sensitive to redox environment, as it is shown that elevated oxidative stress can change its redox state and lead to its deactivation [37]. It is known that sGC is affected by oxidation/loss of the sGC heme, oxidation, or nitrosation of cysteine residues and phosphorylation [38, 39].…”
Section: Discussionmentioning
confidence: 99%